ANALYSIS OF HEALTH WORKERS' PERFORMANCE THROUGH THE DEVELOPMENT OF HUMAN RESOURCES IN PUBLIC HEALTH SERVICE IN INDONESIA AND TIMOR LESTE - Anggi Putri Aria Gita; Oliva Virvizat Prasastin; Nella Tri Surya; Frieda Ani Noor; Sufina Pinto; Agnes Prawistya Sari (The Indonesian Journal of Public Health, 2025)
Introduction: To achieve an ideal and satisfactory level of health for the community, it is very important to provide high-quality services provided by health professionals. Therefore, health workers are expected to show high performance. Based on the 2023 Indonesian Health Profile, 11.5% of community health centers have a shortage of health workers, namely doctors. Timor Leste does not yet have higher education in nursing, so the number of nurses needed is still insufficient. Aims: to analyze the influence of health worker performance on human resource development in the Indonesian and Timor Leste Public Health Services. Methods: A study was conducted involving 43 health professionals. The tool used was a survey conducted through Google Forms. This study used chi-square to investigate the correlation between the two variables and logistic regression to identify the parameters most strongly associated with the performance of health workers. Result: The research findings show that in bivariate analysis, training and work motivation have an impact on the performance of health workers. However, in multivariate analysis, training emerged as the most significant component, with a p-value of 0.021, an odds ratio of 7.173, and a 95% confidence interval of 1.338-8.458. Conclusion: The performance of health workers is largely influenced by their level of training. Health workers with superior training showed 7,173 times more effective performance compared to health workers with poor training. Carrying out regular and continuous training, tailored to the health needs of workers, so that they can master their field of work.